Outcomes of Primigravida with Engaged versus Unengaged Fetal Head at Term: Outcomes of the Primigravida with Fetal Head at Term - Babar, Karishma Anjum; Bukhari, Naila; Babar, Saba Anjum; Pervez, Faryal Shah; Azra, .; Aamir, Seemab (Pakistan Journal of Health Sciences, 2025)
Engagement of the fetal head within the pelvis is an important clinical indicator during pregnancy. Such evaluation guides obstetric decision-making and optimizes maternal and neonatal care. Objectives: To compare the frequency of outcomes in primigravida women with engaged and unengaged fetal heads at term. Methods: This prospective cohort study was carried out in the Department of Obstetrics and Gynecology, Khyber Teaching Hospital, Peshawar, from January 2025 to June 2025. A total of 126 primigravida women were recruited. Data were analyzed using SPSS version 22.0, and relative risk (RR) was calculated for both groups. Results: Among the 126 participants, the mean maternal age was 28.71 ± 6.80 years (range: 18–42 years). The mean birth weight in the engaged group was 3.07 kg. A significant association was observed between fetal head engagement and delivery mode. The unengaged group showed a markedly higher cesarean section rate (63%) compared with the engaged group (21%), with a relative risk of 2.93. Conclusions: Primigravida women with unengaged fetal heads at term had a significantly greater likelihood of cesarean delivery compared with those with engaged heads.